2002
DOI: 10.1039/b209095c
|View full text |Cite
|
Sign up to set email alerts
|

Manganese air exposure assessment and biological monitoring in the manganese alloy production industry

Abstract: One hundred workers carried personal air sampling equipment during three days to assess exposure to inhalable and respirable Mn. A novel four-step chemical fractionation procedure developed for the speciation of Mn in workroom aerosols was applied for selected aerosol filters. Blood and urine samples were analysed for Mn. The geometric mean (GM) concentrations of inhalable (n = 265) and respirable (n = 167) Mn determined in all filters were 254 microg m(-3) and 28 microg m(-3) respectively. Only 10.6% (95% CI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 22 publications
(34 reference statements)
2
49
0
Order By: Relevance
“…The obtained results have shown the high pollution of airborne manganese particles in the studied workplace and it is slightly close to the finding that was reported by Ellingsen et al, revealing the respirable manganese concentration that was 254 μg/m 3 and it assessed within 3 days for 100 of exposed workers [29]. This result is slightly lower than the result that was obtained in the same research [21]; the variety of blood serum samples was the same (N = 100) as in that study: the samples analysis by means of the atomic absorption method showed that the level of manganese in blood's serum was equal to the air pollutants' concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…The obtained results have shown the high pollution of airborne manganese particles in the studied workplace and it is slightly close to the finding that was reported by Ellingsen et al, revealing the respirable manganese concentration that was 254 μg/m 3 and it assessed within 3 days for 100 of exposed workers [29]. This result is slightly lower than the result that was obtained in the same research [21]; the variety of blood serum samples was the same (N = 100) as in that study: the samples analysis by means of the atomic absorption method showed that the level of manganese in blood's serum was equal to the air pollutants' concentrations.…”
Section: Discussionsupporting
confidence: 90%
“…This could suggest that the bioavailability of SiMn is low, because the only difference between 'inhalable Mn' and 'soluble inhalable Mn' is the exclusion of SiMn in the latter marker of exposure. This association has previously not been shown, and should be elucidated further owing to the possible practical consequences (Ellingsen et al, 2003).…”
Section: Discussionmentioning
confidence: 93%
“…A four-step chemical fractionation procedure was applied for the speciation of Mn in a selection of the collected air filters (Thomassen et al, 2001;Ellingsen et al, 2003 (2003) and 'insoluble' Mn digested in aqua regia/hydrofluoric acid (SiMn) (components 4). A total of 199 samples of the inhalable aerosol fraction (in 97 subjects) and 150 respirable aerosol samples (in 53 subjects) were speciated.…”
Section: Air Exposure Assessmentmentioning
confidence: 99%
“…The corresponding geometric mean concentration of "inhalable manganese" is 1270 (range 386-11 457) µg/m 3 (95% CI 944-1711). Between 10% and 11% of the manganese was found in the respirable aerosol fraction (18). These estimates do not consider the impact of exposure duration on the measured serum prolactin concentrations.…”
Section: Discussionmentioning
confidence: 97%
“…All the dose estimates were based on individually collected samples, and they represent the mean value of the available samples for each subject (generally two or three samples for each subject). Extensive details on sampling, speciation, and day-to-day variations in exposure have been presented elsewhere (18,19).…”
Section: Exposure Assessmentmentioning
confidence: 99%